Administrative Suspension of Land Rights Applications on Former HGB Land: A Study of Discretion and Legal Certainty - Widya Ayu Khairunnisa; Andina Elok Puri Maharani; Fatma Ulfatun Najicha (Transpublika Publisher, 2026)
This study addresses the absence of explicit regulatory provisions governing the mechanism for suspending land rights applications; in practice, BPN therefore exercises administrative discretion guided by the principle of prudence and the General Principles of Good Governance (AUPB). Accordingly, this study aims to analyze BPN's authority to suspend applications for Right to Use (Hak Pakai) over land previously encumbered by Building Use Rights (HGB), and to examine the consistency of such decisions with the principles of administrative land law and legal certainty. This study employs a normative legal research method, utilising a legislative, conceptual and case-based approach, through an analysis of legislation and relevant legal literature. The findings indicate that the suspension of applications for Right to Use constitutes an exercise of administrative discretion in the absence of specific legal norms; however, it lacks clear operational parameters, which may potentially result in an overextension of administrative authority in land governance practices. Furthermore, BPN’s considerations are predominantly driven by factual circumstances, such as claims of physical possession by communities, rather than normative considerations, including the priority rights of former HGB holders and the legal appropriateness of land utilization. This condition reflects an imbalance in the application of the principle of legal certainty within land administration. This study concludes that clearer, more operational regulatory frameworks are required to govern the suspension mechanism, define parameters for assessing priority rights, ensure that administrative discretion remains within lawful boundaries, and strengthen legal certainty in land administration.